2012
DOI: 10.1007/s00706-011-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylonitrile fiber mat supported solid acid catalyst for acetalization

Abstract: A novel polyacrylonitrile hybrid fiber mat supported solid acid catalyst was prepared by electrospinning, and its catalytic activities were carefully investigated through acetalization reactions. The results showed that this hybrid fiber mat exhibits high activity for the reactions, with average yields over 95%. Besides having catalytic activities similar to the solid acid, the heterogeneous solid acid/polyacrylonitrile mat can be reused in six runs without significant loss of catalytic activities. The large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Future, it was also found that the yields were too low in the ketalization of cyclopentanone with the three diols (entries 4-6). The similar results were also obtained by Qi et al 31 This fact was attributed to the relative reactivity and stability of cyclohexanone with sixmembered ring in comparison to cyclopentanone with vemembered ring. Furthermore, we compared the catalytic performance of catalyst 3 with the results of other heterogeneous catalysts which published in the literatures (entries 7-10).…”
Section: Effects Of Reaction Parameterssupporting
confidence: 88%
“…Future, it was also found that the yields were too low in the ketalization of cyclopentanone with the three diols (entries 4-6). The similar results were also obtained by Qi et al 31 This fact was attributed to the relative reactivity and stability of cyclohexanone with sixmembered ring in comparison to cyclopentanone with vemembered ring. Furthermore, we compared the catalytic performance of catalyst 3 with the results of other heterogeneous catalysts which published in the literatures (entries 7-10).…”
Section: Effects Of Reaction Parameterssupporting
confidence: 88%
“…PANF-based acid catalyst has similar catalytic activities to the solid acid in acetalation reaction (with yield of 95 %) and could be reused 6 times without significant loss of catalytic activities. [33] Gang Xu et al reported a kind of phosphoric acidfunctionalized PANF catalysts (Figure 2). Experimental results demonstrate that the catalytic activity of fiber catalyst is influenced by the relative polarities of reactants, solvent, and fiber surface.…”
Section: Panf-based Heterogeneous Acid Catalystsmentioning
confidence: 99%
“…prepared a new type of polyacrylonitrile hybrid fiber felt‐supported solid acid catalyst by electrostatic spinning. PANF‐based acid catalyst has similar catalytic activities to the solid acid in acetalation reaction (with yield of 95 %) and could be reused 6 times without significant loss of catalytic activities [33] . Gang Xu et al .…”
Section: Panf‐based Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation